EFFECT OF ADDED METHIONINE TO SOYBEAN MEAL AS A SUBSTITUTE FOR PROTEIN CONCENTRATE IN BROILER STARTER DIET ON SOME PRODUCTIVE TRAITS - RAFH MOHAMMED TAHER (Mesopotamia Journal of Agriculture)
This Experiment was conducted on 120 day old unsexed Ross broiler chicks to study the effect of added methionine to soybean meal as substitute for protein concentrate in the starter ration on some productive traits . The chicks were raised on floor were distributed to three treatments with four replicates each ( 10 birds) . The three experimental starter rations (1-28) day contained 2800 kcal/kg ME and 22% cp . The first supplemented with 5% protein concentrate , while the second and third were with out protein concentrate but supplemented with 0.1 and 0.2% methionine respectively . The Finisher ration (29-49) day contained 3047 kcal/kg ME and 19.19% cp. At 49 day of age 2 birds from each replicate were slaughtered for carcass traits . Statistic analysis of data showed a significant increase (P ≤ 0.05) in body weight , weight gain , feed and protein efficiency ratio for third treatment during (1-28) day , No significant difference in all studied traits during (29-49)day, and the third treatment showed best economic efficiency .